PENGARUH GAYA KEPEMIMPINAN DALAM MENINGKATKAN KINERJA PEGAWAI DI LAPAS KELAS II B BLITAR - Devy Yunitasari; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The figure of a leader to be able to manage and organize the organization to achieve its goals. This study aims to examine the importance of leadership in organizations with a literature approach. This type of research is research with a literature study approach which is carried out by finding theoretical references that are in accordance with the cases obtained. A leader is a positive and confident person who has a vision, mission and high ethical values, with the ability to convey ideas and is able to encourage and relate well with others. Leadership will be a critical success factor in an organization. This is because leadership is the center point for significant changes in the organization, leadership becomes a personality that has an impact and leadership is an art in creating organizational fit and stability. Whatever the organization, formal or informal, must have goals or ideals to be achieved regardless of whether the organization is good or bad. A leadership style that shows, directly or indirectly, about a leader's belief in the abilities of his subordinates. This means that leadership style is behavior and strategy, as a result of a combination of philosophies, skills, traits, attitudes, which are often applied by a leader when he tries to influence the performance of his subordinates. Seeing the real facts that occur, there are many factors that influence the flow of the leadership process, the rest are facts or organizational dynamics that occur. This means that the leader when applying the style or activity of his leadership is very dependent on the pattern of the organization that surrounds him.